EXPLORATION STUDY OF CLIMATE CHANGE MITIGATION USING A PARTICIPATORY DESIGN CHARRETTE APPROACH IN THE ANDIR AREA, BANDUNG CITY, INDONESIA - Abhi Kurniawan; Kelvin Narada Gunawan; Ishma Umni Afiya (Jurnal Pengembangan Kota, 2024)
Climate change poses a challenge for many urban areas worldwide. Inner cities face significant climate change impacts; one such inner city is the Andir Area in Bandung. Andir Area faces climate change issues due to its limited green space coverage of 18.15%, which impacts flood risks and high carbon emissions. However, the Andir Area also has the potential for heterogeneity and societal tolerance. With its potential and challenges, Andir Area can be developed as a climate village prototype, prompting the need for research exploring design strategies to mitigate climate change based on harnessing community heterogeneity. Collaborative planning, such as design charrettes, is one approach that leverages the heterogeneity of a community. This research method is a collaborative experimental study and utilizes design charrettes as an alternative approach to designing a heterogeneous and climate-resilient area. The research findings indicate that the quality of the Andir Area can be enhanced by integrating climate change mitigation with community heterogeneity through participatory design charrettes. The benefit of this research lies in providing insights to reduce the impact of climate change in the Andir Area through community participation. Overall, this article offers valuable perspectives on designing areas that can adapt to the challenges of climate change while preserving social-cultural heterogeneity, acculturation, and tolerance.